2010
DOI: 10.4103/0255-0857.58732
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and detection of Mycobacterium leprae DNA from ZNCF-stained skin smear slides for better identification of negative skin smears

Abstract: Identification of Mycobacterium leprae, which causes leprosy, is done by Ziehl Neelsen Carbol Fuchsin (ZNCF) stained slit skin smear microscopy that aids in the diagnosis and quantification of approximate bacterial load carried by the patient. We attempted M. leprae DNA extraction from 46 stained slit skin smear negative slides, using Proteinase K and SDS lysis, followed by ethanol precipitation. M. leprae specific primers (16SrRNA) were used for PCR-based amplification of DNA. We could detect M. leprae DNA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…In a preliminary trial of 9 independent 3+ positive slides, DNA extraction was attempted by 2 methods: an enzymatic method ( 7 ) and a classical thermic lysis in a Chelex suspension (InstaGene; Bio-Rad, Hercules, CA, USA) ( 8 ). In our study, only the Chelex method produced good results, i.e., enabled us to obtain DNA that was successfully PCR amplified and produced a full spoligotyping pattern (results not shown).…”
Section: The Studymentioning
confidence: 99%
“…In a preliminary trial of 9 independent 3+ positive slides, DNA extraction was attempted by 2 methods: an enzymatic method ( 7 ) and a classical thermic lysis in a Chelex suspension (InstaGene; Bio-Rad, Hercules, CA, USA) ( 8 ). In our study, only the Chelex method produced good results, i.e., enabled us to obtain DNA that was successfully PCR amplified and produced a full spoligotyping pattern (results not shown).…”
Section: The Studymentioning
confidence: 99%
“…DNA was extracted from skin biopsies using the previously described lysis protocol 41 . Briefly, 25 mg of tissue was manually homogenized, mixed with 1 ml of 1X phosphate-buffered saline (PBS), centrifuged at 8600g for 10 min at 4 °C and the pellet was dried for 1 hr.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported successes to detect M . leprae by PCR in SSS showing its clear advantage over SSS microcopy [8,16]. Therefore, the present study was carried on 50 new patients comparing the routine conventional SSS microscopy with PCR on SSS in the leprosy diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The tube containing lysate was centrifuged 30 sec at 10,000 rpm, then vortex for 10–15 sec and again centrifuged for 30 sec. And then it was incubated at 60°C for overnight, then temperature was set at 94°C and the reaction was terminated at 94°C for 15 minutes [16,17]. Then purification of DNA by extraction with Phenol:Choloroform method was done as per the method described elsewhere [18].…”
Section: Methodsmentioning
confidence: 99%